2021
DOI: 10.1177/0363546520988021
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Preoperative Mental Health and Clinically Meaningful Outcomes After Osteochondral Allograft for Cartilage Defects of the Knee: A Machine Learning Analysis

Abstract: Background: Fresh osteochondral allograft transplantation (OCA) is an effective method of treating symptomatic cartilage defects of the knee. This cartilage restoration technique involves the single-stage implantation of viable, mature hyaline cartilage into the chondral or osteochondral lesion. Predictive models for reaching the clinically meaningful outcome among patients undergoing OCA for cartilage lesions of the knee remain under investigation. Purpose: To apply machine learning to determine which preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…28 To determine preoperative factors associated with achieving clinically meaningful benefit after restorative cartilage procedures, Wang et al 27 performed a limited multivariate analysis on a combined cohort of patients treated with autograft mosaicplasty and OCA and reported that patients with lower preoperative activity levels and higher pain symptoms were more likely to fail to achieve meaningful clinical benefit. Although this analysis did not account for mental health, analyze preoperative factors simultaneously, or report predictive model performance, Ramkumar et al 23 applied ML to an OCA cohort of 185 patients and found that those with worse preoperative mental health and higher preoperative knee function were less likely to achieve meaningful clinical benefit in terms of QOL and knee function metrics, consistent with our findings. In the present study, ML was similarly chosen as the ideal process to simultaneously analyze a multitude of preoperative factors (anthropometric data, baseline PROMs, examination findings, imaging findings) reported heterogeneously (binary variables, categorical variables, continuous variables, etc) with unknown or differential weighted value in assessing postoperative clinical benefit.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…28 To determine preoperative factors associated with achieving clinically meaningful benefit after restorative cartilage procedures, Wang et al 27 performed a limited multivariate analysis on a combined cohort of patients treated with autograft mosaicplasty and OCA and reported that patients with lower preoperative activity levels and higher pain symptoms were more likely to fail to achieve meaningful clinical benefit. Although this analysis did not account for mental health, analyze preoperative factors simultaneously, or report predictive model performance, Ramkumar et al 23 applied ML to an OCA cohort of 185 patients and found that those with worse preoperative mental health and higher preoperative knee function were less likely to achieve meaningful clinical benefit in terms of QOL and knee function metrics, consistent with our findings. In the present study, ML was similarly chosen as the ideal process to simultaneously analyze a multitude of preoperative factors (anthropometric data, baseline PROMs, examination findings, imaging findings) reported heterogeneously (binary variables, categorical variables, continuous variables, etc) with unknown or differential weighted value in assessing postoperative clinical benefit.…”
Section: Discussionsupporting
confidence: 85%
“…Patients who demonstrate signs of disproportionately low mental health in light of their injuries warrant counseling that the surgery and rehabilitation may not necessarily translate to perceived clinical benefit owing to the underlying mental state. 23 Moreover, this population may be less motivated to commit to the postoperative rehabilitation. Similarly, patients who catastrophize pain symptoms may have alternative sources of pain or require counseling that surgical treatment of the cartilage lesion is unlikely to resolve all pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 18 articles screened for full text, two studies were excluded due to including the wrong study population from the perspective of this review. One study [ 48 ] included knee arthroscopies and one [ 49 ] patients with osteochondral allograft for cartilage defects. Next, five studies [ 50 54 ] did not calculate MCIDs, even though they researched PROMs in TJA patients.…”
Section: Resultsmentioning
confidence: 99%